How psychologists view and engage with competence in their practice : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Taylor, Kristin (Massey University, 2018)
The purpose of this study was to gain insight into how psychologists view and engage with competence and identify the factors that they determine as supporting or inhibiting competent practice. To date, few studies have examined the elements psychologists identify as shaping the development of their professional competence. It is hoped by doing so, strategies can be implemented that develop, maintain, and enhance competence and encourage active participation in the Continuing Competence Programme (CCP). Having an agreed definition of the qualities required to be competent is essential to evaluate, improve, and ensure quality assurance in psychological practice. Ten psychologists from the clinical and industrial organisational scopes participated. Semi-structured interviews were used; questions were designed to act as prompts and to ensure no relevant themes were overlooked. The interviews were recorded then transcribed and analysed using thematic analysis. Results indicated that while the participants understood the meaning of competent practice, how they relate that to their practice and how this influences their participation in the CCP varies. The participants discussed the value of, and the challenges associated with, achieving, demonstrating, and measuring competence and the consequences this has on their practice, their clients and themselves. They also identified factors that encourage, develop, and maintain competence and those factors that are threats to competence. It is essential to understand how an individual perceives competence as this will determine how they view and engage with competence in their practice. Understanding this will assist with competency development, maintenance, measurement and demonstration across the professional lifespan.
Keywords: Clinical psychology; Practice; Clinical competence; Evaluation; Clinical psychologists; Industrial psychologists; Attitudes